2016
DOI: 10.1007/s12665-015-5138-4
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative impacts of population on river water quality in the Jinshui River basin of the South Qinling Mts., China

Abstract: Increasing population is generally responsible for the degraded river ecosystem. Using regression models and mathematical functions, the research quantitatively estimated the population and elevational gradient effects on river water quality during nine surveys from 2006 to 2008 in the Jinshui River basin of the South Qinling Mts., China. The total factor scores at 11 different sampling sites were calculated in factor analysis and first used as pollution index to represent the water quality levels. Population … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…Further, less correlation between population density and NO 3 − has been shown in other research conducted in Sierra Nevada, California by Dylan S. Ahearn et al [29]. The research conducted on the Jinshui River Basin of the South Qinling Mountains, China, predicted the most correlated water quality parameters, which have strong correlation with population, by defining the linear equations [10]. Comparison of the results for both rivers clearly illustrates the relationship between population and the water quality of the river basin.…”
Section: Analysis Of Water Qualitymentioning
confidence: 87%
See 4 more Smart Citations
“…Further, less correlation between population density and NO 3 − has been shown in other research conducted in Sierra Nevada, California by Dylan S. Ahearn et al [29]. The research conducted on the Jinshui River Basin of the South Qinling Mountains, China, predicted the most correlated water quality parameters, which have strong correlation with population, by defining the linear equations [10]. Comparison of the results for both rivers clearly illustrates the relationship between population and the water quality of the river basin.…”
Section: Analysis Of Water Qualitymentioning
confidence: 87%
“…Therefore, the POP-2 range is suitable for maintaining water quality in class C. Taken together, a watershed with a population density of less than 2375, helps to maintain water quality at a higher level with the classification classes A and B in the river basin, whereas a population density less than 2672 is helpful with regard to class C. This proposed population density can be taken into account when determining the carrying population density of the watersheds. Numerous studies that have been conducted on water pollution in river basins have identified a high correlation between population and water quality parameters [1,4,9,10]. The present study further evaluated the effects and defined threshold values for population density with respect to the classification of water quality in river basins.…”
Section: Quantitative Population Rangementioning
confidence: 91%
See 3 more Smart Citations